Ice-colloidal templated carbon host for highly efficient, dendrite free Li metal anode - Patrike, Apurva; Kaniyamparambil, Karthika; Wahid, Malik; Chaturvedi, Vikash; Shelke, Manjusha (Carbon, 2021)
With its high theoretical specific capacity value, lithium metal itself would be an ideal anode material for rechargeable Li-ion batteries (LIBs). However, practical application of lithium metal is obstructed due to lithium dendrite growth during cycling leads to unstable SEI formation, volume fluctuation and safety hazard. Herein, we have developed a novel high surface area carbon network with both meso (∼20 nm) and micron (∼1–2 μm) size porosity, via ice-colloidal templating, as a scaffold for stable lithium metal anode mitigating lithium dendrite formation. The 3D porous nitrogen doped carbon (3D PNC) network is capable of lithium deposition equivalent to 10 mAhcm−2 at 2 mAcm−2 current density with 99.96% coulombic efficiency for 100 cycles. Moreover, 3D PNC when subjected to 3000 h of continuous plating-stripping measurements (∼700 cycles) depicts the coulombic efficiency of 99.84% with no observable dendrite growth at the current density of 2 mAcm−2 and lithium intake capacity of 5 mAhcm−2. A full cell of lithium plated 3D PNC anode with LiFePO4 shows an excellently stable performance up to 50 cycles at an input current density of 50 mAg−1, with a coulombic efficiency retention of 99.73%.

Insights into electrolyte-solvent interactions and SEI formation for sustainable sodium-ion battery operation at low temperatures - Kim, Soohwan; Mirzapure, Vinay; Atwi, Rasha; Koppisetti, Heramba V. S. R. M.; Wasnik, Kundan; Rajput, Nav Nidhi; Shelke, Manjusha; Pol, Vilas G. (Small Methods, 2025)
Sodium-ion batteries (SIBs) show promise as an alternative to lithium-ion batteries. However, they face performance challenges at ultra-low temperatures (<-40 degrees C) due to slow Na+ transfer kinetics with conventional electrolytes. This limitation restricts their use in extreme environments such as polar regions and outer space. The presented systematic study addresses this challenge by modulating and tailoring the electrolyte composition for SIBs, enabling ultra-low temperature operation down to -110 degrees C for the first time. The comprehensive molecular dynamic and density functional theory calculations combined with experimental Raman spectroscopy and nuclear magnetic resonance studies of advanced electrolytes provided a deeper mechanistic understanding of the solvation structures and their impact on electrochemical performance. By varying the solvent composition with a combination of tetrahydrofuran and 2-Methyltetrahydrofuran solvents and sodium hexafluorophosphate (NaPF6) salt, the freezing point, solubility, and Na+ solvation structure of the electrolyte is modulated and studied in detail. The extensive anion engagement in the optimized mix solvent electrolyte facilitated the formation of a stable and inorganic-rich solid electrolyte interphase layer, ensuring low overpotentials and uniform Na+ deposition, yielding superior cycling stability. As a result, the developed electrolyte enables SIBs to achieve reversible capacities of 88 mAh g(-1) at -60 degrees C and 50 mAh g(-1) at -100 degrees C. These insights may contribute to developing improved energy storage devices suitable for challenging environmental conditions.
Keywords: contact-ion pair; solid electrolyte interphase (SEI); solvation; ultra-low temperature; XPS-depth Profiling